PERANCANGAN APLIKASI MANAJEMEN ASET GEDUNG BERBASIS WEB - Dani Basse; Dea Andini Andriati (Jurnal Komputer dan Teknologi, 2026)
This web-based Office Asset Management application was developed to provide an integrated solution for managing the entire asset cycle within an agency or company. This system facilitates digital recording of asset data, from procurement, placement in a room, borrowing, maintenance, to asset disposal. Key features include asset data management, asset room management, damaged asset recording, maintenance processes, automatic asset depreciation, and report generation and QR Code labels for asset identification. Users can easily input and update asset data, monitor asset status in real-time, and track asset borrowing and maintenance history. The asset borrowing feature allows detailed recording of borrowing and return transactions, while the maintenance feature supports systematic asset maintenance and repair processes. Asset depreciation is calculated automatically according to accounting standards, so asset values ​​are always updated and accurate. A comprehensive reporting system assists management in auditing, evaluation, and data-based decision-making. The QR Code label feature speeds up the inventory process and facilitates asset identification in the field. With the implementation of this application, asset management becomes more efficient, transparent, and accountable, reducing the risk of unmonitored asset loss or damage, and supporting professional and modern asset governance in the workplace